Effect of Intestinal Levodopa-Carbidopa Infusion on Pharyngeal Dysphagia: Results from a Retrospective Pilot Study in Patients with Parkinson's Disease. (11th March 2020) - Labeit, Bendix; Claus, Inga; Muhle, Paul; Suntrup-Krueger, Sonja; Dziewas, Rainer; Warnecke, Tobias
Abstract : Background . Pharyngeal dysphagia is a common symptom of Parkinson's disease (PD) leading to severe complications. PD-related pharyngeal dysphagia (PDrPD) may significantly improve in up to half of patients following acute oral levodopa challenge. Objective . The aim of this study was to investigate the effects of levodopa-carbidopa intestinal gel (LCIG) on PDrPD. Methods . Forty-five PD patients under LCIG treatment were available for retrospective analysis. In all patients with PDrPD who underwent flexible endoscopic evaluation of swallowing (FEES) in the clinical "on-state" both before and after implementation of LCIG treatment, FEES videos were systematically reassessed. PDrPD was characterized using a PD-specific FEES score evaluating premature bolus spillage, penetration/aspiration, and pharyngeal residue. Further, the duration of white-out was assessed, as a parameter for pharyngeal bradykinesia. Results . Eleven patients with PDrPD (mean age 74.6 ± 4.4 years; mean Hoehn and Yahr stage 3.8 ± 0.6) received FEES both before and after the onset of LCIG treatment. The mean swallowing score improved from 14.9 ± 7.3 to 13.0 ± 6.9 after implementation of LCIG; however, this difference was not significant (p = 0.312 ). Premature bolus spillage decreased significantly (p = 0.002 ) from 5.4 ± 1.1 to 3.6 ± 1.0, and white-out duration decreased significantly (p = 0.002 ) from 984 ± 228 ms to 699 ± 131 ms after implementation of LCIG. Conclusions . LCIG may affect PDrPD and reduce premature bolus spillage and pharyngeal bradykinesia. Future studies with larger sample sizes are required to follow-up on these pilot results and identify which factors predict a good response of PDrPD to LCIG treatment.